Systematic Review of Technical Variations for Mohs Micrographic Surgery for Melanoma. Issue 12 (December 2021) - Krausz, Aimee E.; Higgins, H. William; Etzkorn, Jeremy; Sobanko, Joseph; Shin, Thuzar; Giordano, Cerrene; McMurray, Stacy L.; Golda, Nicholas; Maher, Ian A.; Leitenberger, Justin J.; Bar, Anna; Nijhawan, Rajiv I.; et al.
Abstract : BACKGROUND: Mohs micrographic surgery (MMS) for cutaneous melanoma is becoming more prevalent, but surgical technique varies. OBJECTIVE: To define variations in published techniques for MMS for melanoma. METHODS AND MATERIALS: A systematic review was performed of PubMed, EMBASE, and Scopus databases to identify all articles describing surgical techniques for MMS for melanoma. Technical details were recorded for the preoperative, intraoperative, and postoperative phases of MMS. RESULTS: Twenty-four articles were included. Mohs surgeons vary in how they assess clinical margins, how wide a margin they excise on the first MMS layer, and how they process tissue to determine tumor stage and margin clearance during MMS for melanoma. CONCLUSION: Mohs micrographic surgery for melanoma is performed with varied surgical techniques. To establish best practices, additional research is necessary to determine how different techniques affect outcomes. Abstract : Supplemental Digital Content is Available in the Text.